AFFILIATION NEED VIEWED FROM LONELINESS ON STUDENTS LIVING AT DORMITORY OF UNIVERSITY OF SARI MUTIARA INDONESIA INDONESIA MEDAN - Marpaung, Winnida (Psikologi Universitas Sari Mutiara Indonesia, 2018)
This study aims to find out relationship between Loneliness and Affilitation Need. The hypothesis of this study states that there is a negative correlation between loneliness and Affiliation Needs, assuming the higher is Loneliness, the lower will Affiliation Need be and conversely the lower is the loneliness, the higher will Affilitation Need be. The subjects of this study were 142 students living in the dormitory of University of Sari Mutiara Indonesia, who were selected using Isaac Michael table. Data were obtained from a scale to measure Affiliation Needs and Loneliness. The calculation was performed by means of testing requirements analysis (assumption) that consists of normality test and linearity test. The data analysis was performed by using Product Moment Correlation with SPSS 17 for Windows. The results of data analysis showes that a correlation coefficient is -0.514 with p = 0.000 (p <0.05). It shows that there is a negative relationship between Loneliness and Affiliation Needs. These results indicate that the contribution given by Affiliation Need to Loneliness variable is 26.4 percent and the remaining 73.6 percent is influenced by other factors. From these results it is concluded that the hypothesis stating that there is a negative relationship between loneliness and Affiliation Needs, is acceptable.  Keywords : Affiliation Needs, Loneliness